HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DENGAN KETERATURAN MELAKSANAKAN ANTENATAL CARE (ANC) - Rahmawati, Eka; Silaban, Titin Dewi Sartika (JURNAL KESEHATAN TERAPAN, 2021)
Background:Mortality and morbidity in pregnant and maternity women is a big problem in developing countries, around 25-50% of deaths in women of childbearing age are caused by problems related to pregnancy.Objective: This study aims to determine the relationship between knowledge of pregnant women about the danger signs of pregnancy and the regularity of carrying out antenatal care.Methods: The type of research used in this research is correlational analytic method, which is looking for the relationship between one variable and another to determine the relationship between knowledge of pregnant women about the danger signs of pregnancy and the regularity of carrying out Antenatal Care. The design used is cross sectional, which is a research design by measuring or observing at the same time, one time or a study. The sampling technique in this study is non-probability sampling, purposive sampling type, which is a sampling technique with certain considerations, all subjects who meet the inclusion criteria in the study, and obtained as many as 52 respondents. Results: The results showed that there was a relationship between the knowledge ofpregnant women about the danger signs ofpregnancy and theregularity ofcarrying out antenatal care with a p-value of 0.002 (p<0.05).Conclusion: There is a relationship between the knowledge of pregnant women about the danger signs of pregnancy and the regularity of carrying out antenatal care. Key words:Knowledge, Danger Signs of Pregnancy and Antenatal Care